Fast‐Acting Black‐Phosphorus‐Assisted Depression Therapy with Low Toxicity. Issue 2 (28th November 2019) - Jin, Liguo; Hu, Ping; Wang, Yinyin; Wu, Luojia; Qin, Kang; Cheng, Haoxin; Wang, Shuhua; Pan, Bingxing; Xin, Hongbo; Zhang, Wenhua; Wang, Xiaolei
Abstract: A black phosphorus (BP)‐nanosheet‐based drug‐delivery system containing a therapeutic drug (Fluoxetine, Flu) is synthesized. According to subsequent behavioral, biochemical, and electrophysiological analysis, BP‐Flu, after irradiated with near‐infrared light (808 nm), can significantly reduce the therapy time of depression. Meanwhile, the inherent biotoxicity of Flu is also alleviated. Abstract : A black phosphorus (BP)‐nanosheet‐based drug delivery system is developed for synergistic photothermal/chemotherapy of depression. BP nanosheets can improve the biocompatibility of the antidepressant drug Fluoxetine. More importantly, BP–Fluoxetine, under near‐infrared irradiation, greatly shortens the therapy time of depression with no obvious side effects, which has great potential for clinical application in the future.